The Impact of Finance Sharia on Indonesia's Economic Stability - Nahata Purwa Devayanti; Atikah Oktaviani; Risky Aditia; Miftah Syintatoro; Nonik Nonik (Lentera Ilmu Nusantara, 2026)
This study aims to examine the impact of Islamic finance on economic stability at both national (Indonesia) and global levels. In an era of economic uncertainty and global market volatility, Islamic financial systems offer principles of justice, transparency, and social responsibility, which are believed to enhance economic resilience. This research employs a literature review method with a descriptive qualitative approach. The analysis reveals that Islamic financial instruments—such as sukuk, contract-based financing, and zakat play a significant role in stabilizing the real sector and strengthening an inclusive financial system. In Indonesia, the growth of Islamic finance has supported national economic resilience, particularly during times of crisis. Globally, the adoption of Sharia principles by several countries demonstrates the system's potential in sustainable fostering economic stability. This study recommendations strengthening regulatory frameworks and financial literacy to broaden the contribution of Islamic finance to the global economy.